Driving tour of the Upper Wakarusa Watershed - Weir, Arnold (Kansas State University, 2010)
This report presents one approach for increasing understanding, appreciation and protection of watersheds by individuals living within the urban-to-rural lands interface. The purpose of the study is to provide guidance to developing and implementing a driving tour of environmentally sensitive land around Clinton Lake and the Upper Wakarusa Watershed (UWW). Although the tour is particular to the UWW, the principles will be useful to planners and watershed advocates working to promote water quality improvement in other geographic areas. A first step in increasing community involvement to restore and protect watersheds is developing a broader public understanding of what watersheds are and their integral part in daily life. By taking a driving tour (literally or virtually), participants can see firsthand how a watershed functions and the values it provides to people and ecosystems. Two key ingredients in the planning process are public participation and clearly defined goals. Public participation begins with awareness of an issue that impacts lives. The first step in engaging the public is to develop a framework for making residents aware that watersheds are a critical part of their environment and the health of their community. The driving tour of the Upper Wakarusa Watershed should help residents and visitors experience a “sense of place” related to the watershed by achieving three over-arching goals: Develop meaningful themes that engage the residents and visitors in learning about watersheds and give insight to their relationships with the watershed. Introduce concepts that are relevant to the lives of residents and visitors and their understanding of a watershed. Generate a stronger “sense of place” as it relates to the Upper Wakarusa watershed. The driving tour in this report has been designed to serve as a broad blueprint for future implementation. The route was devised to take advantage of area resources, especially those on public land, while adhering to guidelines proven successful in promoting rural areas such as the Flint Hills and Cheyenne Bottoms. The actual implementation of the Upper Wakarusa Watershed Driving Tour is expected to be led by local coalitions, and the precise route should be adjusted as necessary.
Keywords: watershed; driving tour; Upper Wakarusa; Environmental Sciences (0768); Geography (0366); Urban and Regional Planning (0999)